Identification by Photo-Affinity Labeling of the Proteins in Escherichia coli Ribosomes Involved in Elongation Factor G-Dependent GDP Binding - Maassen, J. A. (1974)
Guanosine diphosphate esterified at the β-phosphate group with the photolabile 4-azidophenol [1-(4-azidophenyl)-2-(5′-guanyl)pyrophosphate] was found to inhibit GDP binding to the ribosomes of E. coli. UV-irradiation of the fusidic acid-stabilized complex among ribosomes, elongation factor G, and the azidophenyl-GDP, results in selective attachment of the photo-affinity label to the proteins L5, L11, L13, L18, and L30. In addition, a substantial reduction of the amount of L16 present in irradiated ribosomes was found. Except for L13, no significant reaction of azidophenyl-GDP with the ribosomal proteins was observed when fusidic acid was omitted from the irradiation mixture. The results strongly suggest that L5, L11, L18, and L30 are involved in GDP binding. The possibility of a transient binding of GDP to L13 followed by migration to the actual GTPase site is discussed.